A secure personal health record repository - Pedrosa, Tiago (2013)
Due to strict regulatory, ethic and legal issues, Electronic Health Record (EHR) systems have been mainly deployed in federated health care scenarios. This situation has been hindering the wide adoption of EHRs, contributing to delaying the establishment of a competitive market where contributions from different providers could take full advantage of information exchange and regular practitioners’ collaboration. Moreover, with the increasing awareness of medical subjects, patients are demanding more control over their own personal data - Personal Health Record (PHR). This paper presents a secure PHR repository which access is controlled through the joint use of a Virtual Health Card Service (VHCS) and an access Broker. This solution can be deployed in any public or private storage service since it behaves as a sandbox system which access policy is defined externally. To assure a friendly query-retrieve interaction the whole repository is indexed, and separated clinical events are kept independently to increase the efficiency of cipher and encipher algorithms.